Poor food and nutrient intake among Indigenous and non-Indigenous rural Australian children - Gwynn Josephine D; Flood Victoria M; D'Este Catherine A; Attia John R; Turner Nicole; Cochrane Janine; Louie Jimmy; Wiggers John H (BMC, 2012)
Abstract Background The purpose of this study was to describe the food and nutrient intake of a population of rural Australian children particularly Indigenous children. Participants were aged 10 to 12 years, and living in areas of relative socio-economic disadvantage on the north coast of New South Wales. Methods In this descriptive cross-sectional study 215 children with a mean age of 11.30 (SD 0.04) years (including 82 Indigenous children and 93 boys) completed three 24-hour food recalls (including 1 weekend day), over an average of two weeks in the Australian summer of late 2005. Results A high proportion of children consumed less than the Australian Nutrient Reference Values for fibre (74-84% less than Adequate Intake (AI)), calcium (54-86% less than Estimated Average Requirement (EAR)), folate and magnesium (36% and 28% respectively less than EAR among girls), and the majority of children exceeded the upper limit for sodium (68-76% greater than Upper Limit (UL)). Energy-dense nutrient-poor (EDNP) food consumption contributed between 45% and 49% to energy. Hot chips, sugary drinks, high-fat processed meats, salty snacks and white bread were the highest contributors to key nutrients and sugary drinks were the greatest per capita contributor to daily food intake for all. Per capita intake differences were apparent by Indigenous status. Consumption of fruit and vegetables was low for all children. Indigenous boys had a higher intake of energy, macronutrients and sodium than non-Indigenous boys. Conclusions The nutrient intake and excessive EDNP food consumption levels of Australian rural children from disadvantaged areas are cause for concern regarding their future health and wellbeing, particularly for Indigenous boys. Targeted intervention strategies should address the high consumption of these foods.